2010
DOI: 10.1112/blms/bdq074
|View full text |Cite
|
Sign up to set email alerts
|

Exotic quasi-conformally homogeneous surfaces

Abstract: Abstract. We construct uniformly quasiconformally homogeneous Riemann surfaces which are not quasiconformal deformations of regular covers of closed orbifolds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Since the number of such permutations is finite, there is a uniform constant K ≥ 1 such that the modified map f can be chosen as a K-quasi-isometry on each Q. We can find similar arguments in Bonfert-Taylor et al [12]. Since the action on G induced by f is isometric, we see that such f is a rough-isometry with an additive constant L depending only on S and K. Lifting f to B 2 , we obtain the required rough-isometry f .…”
Section: Kleinian Groups Of Bounded Typementioning
confidence: 56%
“…Since the number of such permutations is finite, there is a uniform constant K ≥ 1 such that the modified map f can be chosen as a K-quasi-isometry on each Q. We can find similar arguments in Bonfert-Taylor et al [12]. Since the action on G induced by f is isometric, we see that such f is a rough-isometry with an additive constant L depending only on S and K. Lifting f to B 2 , we obtain the required rough-isometry f .…”
Section: Kleinian Groups Of Bounded Typementioning
confidence: 56%
“…One might then optimistically hope that every uniformly quasiconformally homogeneous surface is a quasiconformal deformation of a regular cover of a closed hyperbolic 2-orbifold. Bonfert-Taylor, Canary, Souto and Taylor [7] showed that this is not the case. Sketch of proof: Given a connected countable graph X, each of whose vertices has valence d ≥ 3, one may construct a hyperbolic surface S X by "thickening up" X.…”
Section: Sketch Of Proofmentioning
confidence: 99%
“…QCH surfaces that are not quasiconformally equivalent to regular covers of closed orbifolds) is shown. However, all the exotic QCH surfaces constructed in [4] are homeomorphic; in particular, they are homeomorphic to the one-ended infinite-genus surface (affectionately referred to as the Loch Ness monster surface).…”
Section: Introductionmentioning
confidence: 99%